Temporal and Institutional Essence of Non - Performing Assets in Banks : An Indian Scenario - Pillai, K. R. (Indian Journal of Finance, 2018)
The Indian banking system displayed commendable performance even in the wake of the global financial landslide. The entire credit goes to the regulatory framework, which maintains an effective surveillance on the banks in India on an emulative extent. However, the claim of a well-knit banking framework has not translated itself into its capability to insulate the banks from potential credit risk. The accumulation of bad loans poses a threat to the impending erosion of otherwise productive assets within the banks. Though the Indian banking system has moved enormously on the competitive side, from its conventional social banking approach, ever since the new economic policy regime in the early 1990s, non-performing assets (NPAs) still remain an unresolved issue in the country. The present study examined the chronological trends in NPAs in the Indian banking system in the new millennium. The various dimensions of NPAs of public sector banks, private sector banks, and foreign banks in India were examined. The pre-and-post global meltdown trends were compared as part of the study. Fifteen years of data pertaining to NPAs of the financial institutions under study were obtained from the CMIE database and were subject to statistical analysis using SPSS. The outcome of the study gave valuable insights into temporal and institutional implications of NPAs in the banking system of India.